2017
DOI: 10.1007/s40618-017-0616-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of segmental body composition and adiposity hormones on resting metabolic rate and substrate utilization in overweight and obese adults

Abstract: Purpose Low resting metabolic rate (RMR) and high carbohydrate reliance at rest are associated with weight gain, but are highly variable in obese individuals. This study determined the relationship of total and segmental body composition and adiposity hormones with RMR and respiratory exchange ratio (RER) in overweight and obese adults. Methods In 49 men (n=23) and premenopausal women (n=26) (Mean ± SD; Age = 35.0 ± 8.9 yrs; body mass index [BMI] = 33.6 ± 5.2 kg·m−2; percent body fat [%fat] = 40.0 ± 8.0%), R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
2
14
2
2
Order By: Relevance
“…The strong baseline associations we found between FFM and fat mass on one side and RMR on the other side have previously been reported ( 35 ). Interestingly, when comparing intervention-induced changes in Study 2, the association between FFM and RMR disappeared, whereas the association between fat mass and RMR persisted.…”
Section: Discussionsupporting
confidence: 82%
“…The strong baseline associations we found between FFM and fat mass on one side and RMR on the other side have previously been reported ( 35 ). Interestingly, when comparing intervention-induced changes in Study 2, the association between FFM and RMR disappeared, whereas the association between fat mass and RMR persisted.…”
Section: Discussionsupporting
confidence: 82%
“…The 24‐h RQ has been shown to aggregate in family, and it has been suggested that it is at least in part genetically determined . The 24‐h RQ has also been shown to be statistically related to various individual characteristics such as percent body fat, plasma insulin, free fatty acid concentration, sex, ethnicity, age, waist circumference, fat mass and trunk fat mass, and adipocyte size and basal lipolysis measured in isolated hepatocytes from the periumbilical region . However, in perfect energy balance as well as in a given energy imbalance, the 24‐h RQ measured with a stable diet for some days only depends on the macronutrient composition of the diet and energy balance.…”
Section: Significance Of Rqmentioning
confidence: 99%
“…The rate of age-related loss in LM has been shown to be greater in the lower body/legs (Goodpaster et al, 2006;Janssen et al, 2000). Greater leg LM has previously been shown to be associated with a higher resting metabolic rate in both men and women (Hirsch et al, 2017). In addition to LM quantity, muscle quality also declines with age and obesity.…”
Section: Introductionmentioning
confidence: 99%